Singapore's vision of a smart nation - FOO, See Liang (Institutional Knowledge at Singapore Management University, 2016)
With a population of 5.4 million and land area of 718 square kilometres, 94 percent of Singapore’s population live in high-rise apartments, of which, 82 percent dwell in public housing. As an ultra-dense city-state, effective and innovative urban development is a social and economic imperative intricately intertwined with Singapore’s competitiveness and quality of life. Harnessing information and communications technology (ICT) is not only essential to achieving this, but also serves as a template for answering some of the global challenges faced by urban centres around the world–particularly in regard to economic development, social cohesion, better city administration and infrastructure management.